Adaptive and Learning Agents Second Workshop, ALA 2009, Held as Part of the AAMAS 2009 Conference in Budapest, Hungary, May 12, 2009. Revised Selected Papers - Taylor, Matthew E.; Tuyls, Karl.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the thoroughly refereed post-conference proceedings of the Second Workshop on Adaptive and Learning Agents, ALA 2009, held as part of the AAMAS 2009 conference in Budapest, Hungary, in May 2009. The 8 revised full papers presented were carefully reviewed and selected from numerous submissions. They cover a variety of themes: single and multi-agent reinforcement learning, the evolution and emergence of cooperation in agent systems, sensor networks and coordination in multi-resource job scheduling.
Abstraction and Generalization in Reinforcement Learning: A Summary and Framework -- The Effects of Evolved Sociability in a Commons Dilemma -- Replicator Dynamics for Multi-agent Learning: An Orthogonal Approach -- Decentralized Learning in Wireless Sensor Networks -- Recursive Adaptation of Stepsize Parameter for Non-stationary Environments -- Multiagent Reinforcement Learning Model for the Emergence of Common Property and Transhumance in Sub-Saharan Africa -- Learning to Locate Trading Partners in Agent Networks -- Coordinating Learning Agents for Multiple Resource Job Scheduling.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Computer software; Computational complexity; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Discrete Mathematics in Computer Science; Algorithm Analysis and Problem Complexity; Simulation and Modeling; Computer Systems Organization and Communication Networks